DARK PATTERN DALAM APLIKASI DIGITAL FINANCE: PENGARUH DESAIN ANTARMUKA TERHADAP KEPUTUSAN KONSUMEN MENGAMBIL KREDIT DIGITAL - Sadiqin, Amin; Yovita R Pandin, Maria; Kusmaningtyas, Amiartuti (Penerbit Lafadz Jaya, 2026)
The development of digital finance has accelerated public access to digital credit through fintech lending, Paylater, and app-based financing products. However, this ease of access is not always followed by fully autonomous, rational, and informed consumer decisions. This study examines the phenomenon of dark patterns in digital finance applications, namely interface designs that subtly or explicitly direct, pressure, confuse, or manipulate users into making credit decisions that they might not have made if information, time, and alternatives were presented in a balanced manner. Using a qualitative approach based on literature studies and conceptual analysis, this study integrates literature on human-computer interaction, behavioral economics, consumer protection in financial services, and digital finance regulations in Indonesia. The analysis results show that dark patterns influence consumer decisions through four main mechanisms: asymmetry in information visibility, exploitation of cognitive biases, increased friction to refuse or cancel, and data-driven persuasive personalization. In the context of digital credit, these mechanisms can transform credit from a reflective financial decision into an impulsive transactional act. This research offers the concept of the dark credit interface as a novelty, namely a framework for understanding how interface design can weaken consumer protection, increase the risk of over-indebtedness, and challenge conventional oversight models that focus too much on the content of the contract, rather than on the architecture of digital choices before the contract occurs.